Developing 21st Century Skills while teaching Mathematics at School - Subedi, Abatar (Innovative Research Journal, 2024)
This paper aims to explain the ways of supporting to develop 21st century skills through classroom pedagogy by school teachers while teaching mathematics. I used case study research approach and selected seven case respondents (teachers) by using non-probability sampling techniques. I used observation note and interview guidelines to collect the information and analyzed them by using general inductive approach. The findings show that the teachers at institutional schools are using their classroom pedagogies to enhance 21st-centurykills such as critical thinking, creativity, communication, and collaboration while teaching and learning mathematics to some extent. However, there is rare uses of ICT tool to support their classroom pedagogy. Thus, it is suggested that the educators, policy makers and other stakeholders like local government need to reframe their school mathematics curriculum from the perspective to support to enhance 21st century skills among the students.